AKUNTANSI SYARIAH ESENSI, KONSEPSI, EPISTIMOLOGI, DAN METODOLOGI - Mohammad Nizarul Alim (InFestasi, 2011)
A philosophy of accounting is accounting follows the business. In this context, the development of accounting is a response and evaluation of business development. Accounting is not only influenced by the environment and business culture, but also paradigm of accounting scientists. The product will affect the practice of accounting and business climate as well as shape the environment and business culture. One of these is Islamic accounting. Sharia accounting has an important role on consistency in the implementation of Islamic finance. The essence of Islamic accounting based on the paradigm of thinking based on monotheism (tauhid) and the conception of maqhasid sharia, with istimbath. Islamic accounting faces the challenges to explore the concepts that lead to the maqashid sharia in this case the concept of zakat, ma'isyah, trust, ethics, for the reconstruction of financial accounting, management accounting, social accounting, behavioral accounting associated with the development of islamic monetary, fiscal, revitalization of productive and cash waqf, zakat regulations as well as other Islamic economic development.